The Taliban Reader : War, Islam and Politics - Editors by Linschoten, Alex Strick Van and Kuehn, Felix (London Hurst & Company, 2018)
Who are the Taliban? Are they a militant movement? Are they religious scholars? The fact that these and other questions are still raised is testimony to the way the movement has been studied, often at arm$1 (Bs length and with scant use of primary sources. The Taliban Reader forges a new path, bringing together an extensive range of largely unseen sources in a guide to the Afghan Islamist movement from a unique insider perspective. Ideal for students, journalists and scholars alike, this book is the result of an unprecedented, decade-long effort to encourage the emergence of participant-centred accounts of Afghan history. This ground-breaking collection, ranging from news articles and opinion pieces to online publications and poems transcribed by hand in the field, sets the stage for a recalibration of how we understand and study the Afghan Taliban. It challenges researchers to forge new norms in the documentation of conflict and provides insight into the future trajectory of political Islamism in South Asia and the Middle East -- Provided by the publisher.s
Include Index
Keywords: Taliban -- Afghanistan